2003
DOI: 10.1002/food.200390060
|View full text |Cite
|
Sign up to set email alerts
|

Effect of processing on the protein nutritional value of Canavalia gladiata seeds

Abstract: Evaluation of protein true digestibility (TD), biological value (BV), and net protein utilization (NPU) of diets containing mature sword bean (Canavalia gladiata), seed flour and grits were carried out with male Sprague-Dawley rats. The seed flour and grits were processed by soaking, cooking, soaking and cooking, autoclaving, and roasting. The TD of processed flour (cooked (84.8), soaked and cooked (76.2), autoclaved (82.0), roasted grits (64.5), and roasted flour (61.2)) were significantly higher (p < 0.05) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…However, in germinated soybeans increased PD was noticed (Trugo et al ., 2000). Ekanayake et al . (2003) observed decreasing values of the TD as soaking of sword bean ( Canavalia gladiata ) progressed.…”
Section: Discussionmentioning
confidence: 99%
“…However, in germinated soybeans increased PD was noticed (Trugo et al ., 2000). Ekanayake et al . (2003) observed decreasing values of the TD as soaking of sword bean ( Canavalia gladiata ) progressed.…”
Section: Discussionmentioning
confidence: 99%
“…The chemical composition of seeds of sword bean has been reported and compares quite well with soybean [43][44][45]. Average yield ranges from 720 to 1500 kg/ha which can be compared with soybean yield of 600-1000 kg/ha [43,46]. The fruits mature in 6-10 months after planting.…”
Section: Sword Bean (Canavalia Gladiata L)mentioning
confidence: 96%
“…Furthermore, the seed coat of the bean is rich in gallic acid and its derivatives, mainly gallotannins, a common trait found in legume polyphenols [41]. The chemical composition of seeds of sword bean has been reported and compares quite well with soybean [43][44][45]. Average yield ranges from 720 to 1500 kg/ha which can be compared with soybean yield of 600-1000 kg/ha [43,46].…”
Section: Sword Bean (Canavalia Gladiata L)mentioning
confidence: 99%
See 1 more Smart Citation
“…In further studies, Ekanayake et al ( 2003 ) found that true protein digestibility (TD) of processed sword bean seed fl our cooked (84.8), soaked and cooked (76.2), autoclaved (82.0), roasted grits (64.5), and roasted fl our (61.2) were signifi cantly higher than in the raw (51.4) and the soaked only grits (35.8). Soaking the grits lowered TD.…”
Section: Nutritive/medicinal Propertiesmentioning
confidence: 96%